Automated Retrieval of Non-Engineering Domain Solutions to Engineering Problems - Stroble, J. K.; Stone, R. B.; McAdams, D. A.; Goeke, M. S.; Watkins, S. E. (Cranfield University Press, 2009)
Biological inspiration for engineering design has occurred through a variety of techniques such as creation and use of databases, keyword searches of biological information in natural-language format, prior knowledge of biology, and chance observations of nature. This research focuses on utilizing the reconciled Functional Basis function and flow terms to identify suitable biological inspiration for function based design. The organized search provides two levels of results: (1) associated with verb function only and (2) narrowed results associated with verb-noun (function-flow). A set of heuristics has been complied to promote efficient searching using this technique. An example for creating smart flooring is also presented and discussed.
Organised by: Cranfield University
Keywords: Engineering design, Function; Function; Biomimicry; Information retrieval